Analisis Niat Pembelian Produk Makanan Halal Berdasarkan Theory of Planned Behavior pada UMKM Virgin Cake & Bakery - Bagus Dwi Atmoko; Ibnu Khajar (Lembaga Yasin AlSys, 2026)
Micro, small, and medium enterprises (MSMEs) play a strategic role in supporting national economic growth, including in the halal food sector, which continues to expand in line with increasing consumer awareness; consequently, understanding consumer behavior, particularly the factors influencing purchase intention, has become increasingly important. This study aimed to analyze the influence of attitude toward behavior, subjective norm, and perceived behavioral control on purchase intention for halal food products using the Theory of Planned Behavior (TPB) framework. A quantitative approach with a survey method was employed, in which primary data were collected via questionnaires from 100 consumers of the MSME Virgin Cake & Bakery in Semarang City, selected using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that attitude toward behavior, subjective norm, and perceived behavioral control had a positive and significant effect on purchase intention for halal food products. These findings confirm that consumer attitudes, social influences, and perceptions of ease and capability in making purchases play an important role in shaping purchase intention. The practical implications of this study provide guidance for MSME actors in formulating marketing strategies oriented toward strengthening consumers’ positive attitudes, optimizing social support, and enhancing ease of access to halal products in order to reinforce competitiveness and business sustainability.